2016
DOI: 10.4265/bio.21.153
|View full text |Cite
|
Sign up to set email alerts
|

Antifreeze Activity of Xylomannan from the Mycelium and Fruit Body of <i>Flammulina velutipes</i>

Abstract: An identified class of antifreeze, a xylomannan-based thermal hysteresis TH -producing glycolipid, has been discovered from diverse taxa, including plants, insects, and amphibians. We isolated xylomannan from the mycelium and fruit body of the basidiomycete Flammulina velutipes using successive hot extraction with water, 2% and 25% aqueous KOH, and gel filtration chromatography. The xylomannan from the fruit body had a recrystallization inhibiting RI activity RI=0.44 at 0.5 mg/mL. The dried weight yield of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 28 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Little is known about the role of xylose in the fungal cell walls. It could potentially be a component of xylomannan, which has been detected in the cell walls of Flammulina velutipes and Trichosporon cutaneum ( Depree et al, 1993 , Kawahara et al, 2016 ) and is found in diverse taxa, ranging from plants, insects, and amphibians ( Walters et al, 2011 ). Xylomannan has been proposed to act as an antifreeze molecule that enables organisms to overwinter.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the role of xylose in the fungal cell walls. It could potentially be a component of xylomannan, which has been detected in the cell walls of Flammulina velutipes and Trichosporon cutaneum ( Depree et al, 1993 , Kawahara et al, 2016 ) and is found in diverse taxa, ranging from plants, insects, and amphibians ( Walters et al, 2011 ). Xylomannan has been proposed to act as an antifreeze molecule that enables organisms to overwinter.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of branched 1,4 xylosyl residues is novel and has not yet been reported in fungi. It was previously suggested that xylosyl residues in the Bgh cell wall may form xylomannan, an antifreeze molecule ( Pham et al, 2019 ), as xylomannan has been detected in the cell walls of other fungal species ( Walters et al, 2011 , Kawahara et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Antifreeze molecules such as antifreeze proteins, polysaccharides such as xylomannan, and glycolipids have been found in various organisms that exhibit freezing tolerance (Walters et al 2009, Duman 2015, Kawahara et al 2016, Kim et al 2017. The freezing point of antifreeze proteins and xylomannan drops by at most 3−4℃ (Walters et al 2009, Kim et al 2017.…”
Section: Resultsmentioning
confidence: 99%